Kejadian Takut Jatuh Pada Lansia yang Tinggal di Komunitas - Anggarani, Anastasia Putu Martha; Djoar, Raditya Kurniawan (STIKes Panti Rapih, 2025)
Fear of falling in the elderly occurs due to the elderly's lack of self-confidence in carrying out activities independently. This can cause a decrease in the quality of life for the elderly. This study aims to identify the incidence of fear of falling among the elderly who live in the community so that appropriate interventions can be determined to handle it. This research is a descriptive study involving 77 elderly people who live in the community. The instrument of this study was the Modified Falls Efficacy Scale-Indonesian Version (Modified FES-I) questionnaire. The results of this study indicate that 66.3% of the elderly experience high anxiety about falling. Balance when moving or walking is carried out by several systems in the body. In the aging process, the elderly experience a decrease in anatomical and physiological functions, resulting in a reduced ability to maintain balance and causing them to often fall during activities. This situation reduces the confidence of the elderly in carrying out activities independently, so they feel afraid of falling